(untitled) (Journal of Social Sciences Review, 2025)
Entrepreneurship is an important driver of economic growth, innovation, and job creation. For developing countries like Pakistan, understanding what influences students’ intentions to start a business can help strengthen the entrepreneurial culture. This study examines how entrepreneurial education, entrepreneurial alertness, and entrepreneurial passion shape the intentions of university students in Khyber Pakhtunkhwa (KP) to pursue entrepreneurship A quantitative, cross-sectional design was used. Data came from 295 final-year business and commerce students in 17 public universities across KP. A structured questionnaire based on established scales from Linan and Chen (2006), Kaish and Gilad (1991), Phan et al. (2002), and Cardon et al. (2013) measured the core variables. SPSS v26 was used for descriptive analysis, correlations, and multiple regression. Reliability scores ranged from 0.70 to 0.87. Entrepreneurial education (β = 0.53, p < .001) and entrepreneurial passion (β = 0.50, p < .001) both showed strong positive effects on entrepreneurial intentions. Entrepreneurial alertness (β = 0.21, p < .05) had a smaller but positive impact. Together, the three predictors explained 48.8% of the variance in intentions (R = 0.699; R² = 0.488). Findings show that entrepreneurship education and the development of passion are key to encouraging students toward entrepreneurial careers, while alertness adds supportive influence. Universities should integrate practical experience and motivation-building elements to strengthen students’ readiness to become entrepreneurs.